Analisis SWOT Perkembangan Dana Haji di Indonesia : Studi Pendekatan NVivo dan Literatur Review - Rohmadi; Doni Yusuf Bagaskara; Indah Yuliana (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
This study aims to determine the SWOT analysis of the potential for Hajj Fund Development in Indonesia using the NVivo approach. This research uses qualitative methodology with Nvivo approach and literature review. "Data analysis techniques include: (1) mapping the number of news article codes based on SWOT analysis, namely (strengths, weaknesses, opportunities and threats), around the "Hajj Fund" using NVivo 14 software; (2) mapping the results of visualization with hierarchical diagrams and testing the correlation of relationships between media articles using SWOT Analysis; (3) map the research topic with Worldcloud or a collection of words that are often discussed in media articles; and (4) Testing the significant value between media articles to determine the magnitude or size of a correlation around the topic of "Hajj Fund". The results of this study show that the topics that are often discussed in media articles about the Hajj Fund are challenges and opportunities. While topics that are rarely discussed by media articles regarding the Hajj Fund are weaknesses and strengths. The implications of this study show that the SWOT study and the resulting Literature Review become recommendations for improving Hajj fund management in the future.